American journal of physical anthropology - Hrdlička, Aleš; Wistar Institute of Anatomy and Biology; American Association of Physical Anthropologists; American Association of Physical Anthropologists. Annual meeting (Publicación (Pan American Institute of Geography and History), 1918)
Volumes for 1930- include the Proceedings of the annual meeting of the American Association of Physical Anthropologists (sometimes issues as separately paged supplements); later issued separately as: Program of the ... Annual Meeting of the American Association of Physical Anthropologists, 1991- (alternates supplement numbering with: Yearbook of physical anthropology).
Keywords: Physical anthropology : Periodicals; Anthropology; Anthropology; Anthropologie physique : Périodiques; Anthropologie; anthropology; Physical anthropology; Anthropologie; Zeitschrift; Online-Ressource; Fysische antropologie